Electrospun gelatin-based scaffolds as a novel 3D platform to study the function of contractile smooth muscle cells in vitro. (10th July 2018) - Bridge, J C; Amer, M; Morris, G E; Martin, N R W; Player, D J; Knox, A J; Aylott, J W; Lewis, M P; Rose, F R A J
Abstract: Contractile dysfunction of smooth muscle (SM) is a feature of chronic cardiovascular, respiratory and gastro-intestinal diseases. Owing to the low availability of human ex vivo tissue for the assessment of SM contractile function, the aim of this study was to develop a novel in vitro SM model that possesses the ability to contract, and a method to measure its contractility. A range of electrospun scaffolds were produced from crosslinked gelatin and methacrylated gelatin (GelMA), generating highly aligned scaffolds with average fibre diameters ranging from 200 nm to several micrometres. Young's moduli of the scaffolds ranged from 1 × 10 5 to 1 × 10 7 Pa. Primary aortic smooth muscle cells (AoSMCs; rat) cells readily adhered to and proliferated on the fibrous scaffolds for up to 10 days. They formed highly aligned populations following the topographical cues of the aligned scaffolds and stained positive for SM markers, indicating a contractile phenotype. Cell-seeded GelMA scaffolds were able, upon stimulation with uridine 5′-triphosphate (UTP), to contract and their attachment to a force transducer allowed the force of contraction to be measured. Hence, these electrospun GelMA fibres can be used as biomimetic scaffolds for SM cell culture and in vitro model development, and enables the contractile forces generated by the aligned three-dimensional sheet of cells to be directly measured. This will supplement in vitro drug screening tools and facilitate discovery of disease mechanisms.